2004
DOI: 10.1128/iai.72.11.6554-6560.2004
|View full text |Cite
|
Sign up to set email alerts
|

Association of iss and iucA , but Not tsh , with Plasmid-Mediated Virulence of Avian Pathogenic Escherichia coli

Abstract: Avian pathogenic Escherichia coli (APEC) is an economically important respiratory pathogen of chickens worldwide. Factors previously associated with the virulence of APEC include adhesins, iron-scavenging mechanisms, the production of colicin V (ColV), serum resistance, and temperature-sensitive hemagglutination, but virulence has generally been assessed by parenteral inoculation, which does not replicate the normal respiratory route of infection. A large plasmid, pVM01, is essential for virulence in APEC stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
1
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(100 citation statements)
references
References 31 publications
5
84
1
5
Order By: Relevance
“…TraT and Iss are believed to prevent deposition of the membrane attack complex of complement by an unknown mechanism. TraT is thought to antagonize C3 deposition (Agü ero et al, 1984) and to inhibit formation of the C5b6 complex (Pramoonjago et al, 1992) (Mellata et al, 2003a) but it is required for full virulence (Tivendale et al, 2004). It has already been suggested that there could a compelling but imperfect relationship between complement resistance, virulence and the presence of iss (Nolan et al, 1992a), and that high resistance to complement may be necessary but not sufficient for virulence (Chaffer et al, 1999).…”
Section: Progress Towards Unravelling Apec Virulence Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…TraT and Iss are believed to prevent deposition of the membrane attack complex of complement by an unknown mechanism. TraT is thought to antagonize C3 deposition (Agü ero et al, 1984) and to inhibit formation of the C5b6 complex (Pramoonjago et al, 1992) (Mellata et al, 2003a) but it is required for full virulence (Tivendale et al, 2004). It has already been suggested that there could a compelling but imperfect relationship between complement resistance, virulence and the presence of iss (Nolan et al, 1992a), and that high resistance to complement may be necessary but not sufficient for virulence (Chaffer et al, 1999).…”
Section: Progress Towards Unravelling Apec Virulence Factorsmentioning
confidence: 99%
“…Notably, a 94 kb region of a 180 kb ColV plasmid carries genes encoding for iron acquisition and transport systems, and these are more prevalent in APEC than avian faecal Escherichia coli (AFEC) . Importantly, a link between APEC virulence and possession of ColV plasmids has been revealed by several studies (Ginns et al, 2000;Johnson et al, 2002;Gibbs et al, 2003;Tivendale et al, 2004). Transformation of an avirulent wild-type E. coli strain with a recombinant plasmid (pHK11) encoding for colicin V led to increased colonization of the chicken trachea (Wooley et al, 1998).…”
Section: The Apec Pathotypementioning
confidence: 99%
“…It has been reported elsewhere (14,16,19) that APEC expresses many virulence-associated traits such as adhesion to the host cells, resistance to host anti-bactericidal activity, iron uptake systems, and the production of hemolysins and other toxins. Some of these traits are encoded chromosomally (11,15): fimC and papC responsible for adhesion factors F1 and P fimbriae, respectively, irp2 and fyuA for iron uptake systems, astA and vat for heat-stable toxin and vacuolating autotransporter toxin, respectively (7).…”
mentioning
confidence: 99%
“…While the genes were found in higher frequency in symptomatic birds, some virulence genes were also present in asymptomatic individuals. has been correlated with highly pathogenic strains 23 .…”
Section: Discussionmentioning
confidence: 99%
“…These genes encode proteins that facilitate the air sac colonization, iron uptake and serum survival in extraintestinal infections 16,17,21,23 .…”
Section: Discussionmentioning
confidence: 99%